Core values for ideal civil servants: Service-oriented, responsive and dedicated - Neo, S., Grmmelikhuijsen, S.and Tummers, L. (Public Administration Review)
What do citizens want? How do citizens think public servants should behave? Although such questions seem straightforward, little is known about the values citizens expect public servants to uphold. This paper therefore identifies such values through extensive coding of qualitative data from representative samples of United States (n = 395), Dutch (n = 369), and South Korean (n = 379) citizens. Surprisingly, and contrasting to assumptions in the literature on citizen satisfaction, citizens hardly value effectiveness, efficiency, and accountability. In contrast, we found that the top three universal values that citizens desire from public servants are serviceability, responsiveness, and dedication. These values are generic across countries, age, gender, and education level. However, some values are more important in some countries than in others. These differences show the influence of a country's longstanding public administrative tradition and its current situation. Our findings challenge scholars and government officials to rethink what citizens want from their civil servants.- Reproduced